2015
DOI: 10.1007/s40264-015-0296-6
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 Inhibitors and Neurocognitive Adverse Events: Exploring the FDA Directive and a Proposal for N-of-1 Trials

Abstract: Proprotein convertase subtilisin-kexin type 9 (PCSK9) inhibitors are a novel class of medications that greatly lower low-density lipoprotein cholesterol (LDL-C) by upregulating LDL receptor availability. In early 2014,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 53 publications
1
46
0
1
Order By: Relevance
“…Although it should be noted that these events are uncommon and that adverse event reporting is not part of a systematic evaluation of neurocognitive function, currently available trial evidence suggests that neurocognitive adverse events may occur more frequently in individuals receiving proprotein convertase subtilisin-kexin type 9 inhibitors independently of on-treatment LDL levels. 15 At the same time, high-dose monthly regimens of proprotein convertase subtilisin-kexin type 9 monoclonal antibodies are known to produce substantial fluctuations of LDL-C between doses. 16 On the basis of our results, this increased variability could possibly contribute to the observed higher rate of neurocognitive events and should be examined by currently ongoing proprotein convertase subtilisin-kexin type 9 trials.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it should be noted that these events are uncommon and that adverse event reporting is not part of a systematic evaluation of neurocognitive function, currently available trial evidence suggests that neurocognitive adverse events may occur more frequently in individuals receiving proprotein convertase subtilisin-kexin type 9 inhibitors independently of on-treatment LDL levels. 15 At the same time, high-dose monthly regimens of proprotein convertase subtilisin-kexin type 9 monoclonal antibodies are known to produce substantial fluctuations of LDL-C between doses. 16 On the basis of our results, this increased variability could possibly contribute to the observed higher rate of neurocognitive events and should be examined by currently ongoing proprotein convertase subtilisin-kexin type 9 trials.…”
Section: Discussionmentioning
confidence: 99%
“…Si bien deberá observarse que estos eventos son infrecuentes y que la notificación de eventos adversos no forma parte de una evaluación sistemática de la función neurocognitiva, la evidencia actualmente disponible de los estudios indica que los eventos adversos neurocognitivos pueden presentarse con más frecuencia en individuos que reciben inhibidores de la proproteína-convertasa subtilisina-kexina tipo 9 independientemente de los niveles de LDL durante el tratamiento. 15 Al mismo tiempo, se sabe que los regímenes mensuales de dosis altas de anticuerpos monoclonales anti proproteína-convertasa subtilisina-kexina tipo 9 producen fluctuaciones sustanciales del LDL-C entre las dosis. 16 Sobre la base de nuestros resultados, este aumento de la variabilidad posiblemente podría contribuir a la mayor tasa observada de eventos neurocognitivos y deberá ser investigada por los estudios actualmente en curso de la proproteína-convertasa subtilisina-kexina tipo 9.…”
Section: Discussionunclassified
“…More recently, we have noted white adipose tissue anomalies in a PCSK9 Q152H female subject (Wassef et al 2015). It has been recommended that patients treated with anti-PCSK9 drugs be monitored for adverse neurocognitive effects (Swiger & Martin 2015). For our part, we plan to verify whether the remarkable lifelong hypocholesterolemia observed in our PCSK9 Q152H carriers might protect them from cognitive impairment of cerebrovascular origin and/or of Alzheimer's degeneration.…”
Section: From Proenzymes (Pcsk1-8) To Pcsk9 As An Escort Proteinmentioning
confidence: 95%
“…One study showed increased levels of β-site amyloid precursor protein cleaving enzyme 1 (the rate-limiting enzyme for generation of amyloid β-peptide) and amyloid β-peptide in PCSK9 −/− mice, 64 whereas another study reported no change in either β-site amyloid precursor protein cleaving enzyme 1 or amyloid β-peptide. 65 As recently reviewed elsewhere, 66 there is controversy concerning the potential for PCSK9-based therapies to cause neurocognitive impairment, an effect theoretically ascribed to the recognized ability of PCSK9 inhibitors to dramatically lower LDL-C, which has raised concern that this may affect central nervous system function. On the one hand, the brains of PCSK9 −/− mice showed no gross structural differences compared with wild-type mice, suggesting no adverse effect of PCSK9 deficiency on brain development, 67 although the applicability of this finding to humans is uncertain.…”
Section: Brainmentioning
confidence: 99%